Wikipedia in the classroom? Perceptions and attitudes of transfer students towards the use of Wikipedia - Malissa Maria Mahmud, * (2012)
This paper provides a description of how Wikipeda was incorporated as a pedagogical means in the ESL settings and reports on the students' attitude and perception on the use of Wikipedia to enhance their L2 proficiency specifically their writing skills.Th experience involved the use of wiki technology and the advanced collaborative forms and participative assessment as part of the teaching method. The results indicate they perceived that the use of Wikipedia had generally enhanced their L2 skills such as reading and writing, expanded their social circles, improved their communication skills and minimized their apprehension when learning and using the language among their peers.